AN ANALYSIS OF COOPERATIVE PRINCIPLE IN TITANIC MOVIE: PRAGMATICS APPROACH - Nurul Athalla Rania Insyira; Zia Hisni Mubarak ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2024)
The approach of this research is pragmatics. Pragmatics is a science of linguistics that learn about the meaning of a sentence or utterance based on the context of the sentence or utterance being discussed. This research focused on the types of cooperative principle that contains in the titanic movie. The aim of this research is to find out types of maxims and examine of the maxims types. The dialogue of the movie showed that this film shows the conversation between superiors and subordinates based on class, namely upper class/class and lower class/class. Based on data that the researcher found from this movie, it is shows that their used cooperative principle in their dialogue. The difference between these groups is that there are no multiple interpretations or misunderstandings in their discussions. In this research applied theory from Grice specifically for the types or rules of maxims. This is research is descriptive qualitative and to collect the data the method is observational method. To analyze the data the method is pragmatic identity. The result of analysis the data are maxims of quantity, maxims of quality, maxims of relations, and maxims of manner. In the conversation of the participants in the movie who used the cooperative principle it will manage the aim or the meaning that being discussed.